Dolines evolution in the Syrian coastal mountains /Qardaha area/ Jawbat Burghal model - Halima, Abed AL Kareem; Saied, William (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
General high mountains of the coast and the tops of the mountains of Qerdaha are particularly characterized by the presence of Karst features resulting from a combination of structural factors that ensured suitable for creating this distinctive Geomorphological appearance conditions, Tectonic factor is responsible for the presence of cracks weaking the rocks as well as for volcanism factor, Whereas the Geological factor is responsible for the appearance of Jurassic rocks on the surface which are appropriate for the emergence of Karst and the direction of the water flow towards the Earth’s interior, While the topographic factor is responsible for the stagnation of water on the semi-flat rocky strata and on some sites that its surface allows the stagnant of water. The most important of those forms are Karst lacunae that apper such as digging deep in Qerdaha mountain of peaks. Find sheds light on the reality , which was formed by Jawbat Burghal as a model to explain the mechanism as the lacunae of the mountains of Alshaara and the reasons for non-proliferation and the future of its development.